A Prediction Model for Various Treatment Pathways of Upper Extremity in Tetraplegia - Bersch, Ines; Krebs, Jörg; Fridén, Jan (Frontiers in Rehabilitation Sciences, 2022)
Upper extremity function is essential for the autonomy in patients with cervical spinal cord injuries and consequently a focus of the rehabilitation and treatment efforts. Routinely, an individualized treatment plan is proposed to the patient by an interprofessional team. It dichotomizes into a conservative and a surgical treatment pathway. To select optimal pathway, it is important to use predictors that substantiate the treatment strategy. Apart from standard assessments, (Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI), the manual muscle test (MRC) and lower motoneuron integrity of key actuators for hand function performed by motor point (MP) mapping might serve as possible predictor. Type of damage, (upper motor neuron (UMN) or lower motor neuron (LMN) lesion) influences hand posture and thus treatment strategy as positioning and splinting of fingers, hands, and arms as well as surgical reconstructive procedures (muscle-tendon or nerve transfers) in choice and timing of intervention. For this purpose, an analysis of a database comprising 220 patients with cervical spinal cord injury is used. It includes ISNCSCI, MRC and MP mapping of defined muscles at selected time points after injury. The ordinal regression analysis performed indicates that MP and ASIA impairment scale (AIS) act as predictors of muscle strength acquisition. In accordance with the innervation status defined by MP, electrical stimulation (ES) is executed either via nerve or direct muscle stimulation as a supplementary therapy to the traditional occupational- and physiotherapeutic treatment methods. Depending on the objective, ES is applied for motor learning, strengthening or maintenance of muscle contractile properties. By employing ES, hand and arm function can be predicted by MP and AIS and used as the basis for providing an individualized treatment plan.